Financial analysis of an oat mill location and timing of the investment - Schuele, Michael (Kansas State University, 2016)
The oat processing industry is a competitive industry and maintaining a cost advantage is important for the industry supply chain. General Mills continuously looks to maintain a competitive advantage in the oat supply chain because it is important for strategic short and long term planning. The purpose of this thesis is to analyze supply chain scenarios to determine where future investments should be made. The analysis looks at an existing location, a refurbished location and a Greenfield site. The analysis projects income statements and net cash flows to determine the conclusions using Net Present Value. The question answered is "Should the company continue to invest in the existing supply chain or should it look to different alternatives in the form of a refurbished or Greenfield plant site for production of oat flour?" The analysis found important relationships between the variables that can influence net cash flow and ultimately NPV. However, given the information from this analysis, a determination was made that the existing facility is still the best investment. Future analysis should be used and the company should plan to analyze this issue again in a five to ten year time frame to maintain its competitive advantage.
Keywords: Net present value; Oat milling; Plant location; Oat supply chain